2016
DOI: 10.18331/brj2016.3.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Recent updates on lignocellulosic biomass derived ethanol - A review

Abstract: HIGHLIGHTSCellulosic biomass is the only source for sustainable fuels.Ethanol is a promising fuel candidate for near/long term applications.Ethanol can also serve as a precursor for other fuels and chemicals.However, processing cost for 2G ethanol is still high.Thus, urgent research efforts are needed to bring the cost down. Lignocellulosic (or cellulosic) biomass derived ethanol is the most promising near/long term fuel candidate. In addition, cellulosic biomass derived ethanol may serve a precursor to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
94
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(104 citation statements)
references
References 57 publications
(65 reference statements)
1
94
0
7
Order By: Relevance
“…Variations of SGA in which modified or heterologous genes are crossed into the deletion collection are also a powerful tool. Thus, their findings have potential implications for biofuel production, which is limited in part by the challenges associated with xylose fermentation (Kumar, Tabatabaei, Karimi, & Horváth, 2016). Thus, their findings have potential implications for biofuel production, which is limited in part by the challenges associated with xylose fermentation (Kumar, Tabatabaei, Karimi, & Horváth, 2016).…”
Section: Technological Innovations Involving Budding Yeastmentioning
confidence: 95%
See 1 more Smart Citation
“…Variations of SGA in which modified or heterologous genes are crossed into the deletion collection are also a powerful tool. Thus, their findings have potential implications for biofuel production, which is limited in part by the challenges associated with xylose fermentation (Kumar, Tabatabaei, Karimi, & Horváth, 2016). Thus, their findings have potential implications for biofuel production, which is limited in part by the challenges associated with xylose fermentation (Kumar, Tabatabaei, Karimi, & Horváth, 2016).…”
Section: Technological Innovations Involving Budding Yeastmentioning
confidence: 95%
“…For example, this strategy helped researchers identify genes that regulate metabolism of the fivecarbon sugar xylose (Usher et al, 2011), which is abundant in cellulose. Thus, their findings have potential implications for biofuel production, which is limited in part by the challenges associated with xylose fermentation (Kumar, Tabatabaei, Karimi, & Horváth, 2016).…”
Section: Technological Innovations Involving Budding Yeastmentioning
confidence: 99%
“…So, other renewable sources of biofuels are highly demanded. Ligno‐cellulosic biomass, present in nature in form of wooden barks of various plants, are huge source of cheap energy having the potential to be converted into variety of biofuels and fine chemicals . The ligno‐cellulosic biomass contains 30–60% cellulose, 20–40% hemicellulose and 10–25% lignin forming hetero matrix which are interconnected .…”
Section: Application Of Surfactantsmentioning
confidence: 99%
“…A recent study by Johnson [35] assessed the production cost of cellulosic ethanol with an integrated enzyme production method to be $0.62 to $0.73 per liter. A detailed review of recent technological progress is available by Kumar et al [36]. On the industry side, a report from POET LLC indicated that their 2009 cost was $0.62/L [37].…”
Section: Production Cost and Uncertaintymentioning
confidence: 99%